Syntax means of expressing emotions “sadness” (based on lyrics by Lina Kostenko) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
In the article clarifies that the problem of verbal representation of emotions is relevant for modern linguistic, because during studing of the language of the text, exept logical-subject semantics, which reflects the concept of human thinking, it is important to take into account also its emotional aspect; analyzed the basic approaches to the definition of the essence of the concepts of “emotion”, “emotionality”, “emotivity”; it is noted that emotions are a subjective relation of a person to objects and phenomena of the surrounding reality, it is emphasized that emotivity is a semantic property of a language with the help of a system of various means to express emotionality as a fact of the psyche.In the proposed study provides classification of emotional states, it is emphasized that all basic emotions can be constructive, that have a positive value for a person, it is found that emotion of sadness can accompany both positive (constructive) experiences and feelings of a person; reviewed categorical nature of emotivity, peculiarities of verbal representation of emotions; It is noted that the verbal representation of emotion of sadness at the syntactic level is facilitated by structural formations with a certain emotivity code that express emotivity due to an unusual syntactic structure; found that syntactic means of expressing emotion of sadness are occasional, informative, inductive, inverted sentences, inserts, repetitions, interruptions, incompleteness of syntactic structures, parsed structures.
Keywords: emotions; constructive emotions; emotionality; emotivity; syntactic means of expressing emotions